Influence of Reaction Conditions on Lignin Hydrothermal Treatment - Erdocia, Xabier; Prado, Raquel; Corcuera, M. Ángeles; Labidi, Jalel (Frontiers in Energy Research, 2014)
Organosolv lignin, obtained from olive tree pruning under optimized conditions, was subjected to a hydrothermal depolymerization process catalyzed by sodium hydroxide. The depolymerization of lignin was carried out at 300°C using different reaction times (20, 40, 60, 70, 80, 90, and 100 min) in order to study the influence of this parameter on lignin depolymerization. The resulting products (oil and residual lignin) were measured and analyzed by different techniques (GC/MS, high-performance size-exclusion chromatography, and pyrolysis–GC/MS) in order to determine their nature and composition. Coke was also formed, at a lower quantity, uncompetitive repolymerization reactions during the lignin hydrothermal treatment. The maximum oil yield and concentration of monomeric phenolic compounds was obtained after 80 min of reaction time. The highest reaction time studied (100 min) had the worst results with the lowest oil yield and highest coke production.